Significance of Various Ᾱsanas in Yoga philosophy: Positive Influence on Health - Shadangi, Bijaya Kumar (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
In the Yoga Philosophy, āsana plays an important role to strengthen the muscles, joints, ligaments and tendons of the body. Regular practice of āsana maintains the physical body in an optimum condition and promotes health. The dormant energy potential is released and experienced with the increased confidence in each and every stage of life. One cultivates awareness, relaxation, concentration and meditation. There is development of the good physical health by stretching, massaging and stimulating the prāṇic channels and internal organs. Without āsana one individual may not stay fit, so it is essential for every individual to practice āsana every day for mental as well as pical health.